Insulin-like growth factor I binding in hepatocytes from human liver, human hepatoma, and normal, regenerating, and fetal rat liver. - Caro, Jose F.; Poulos, John; Ittoop, Olivia; Pories, Walter J.; Flickinger, Edward G.; Sinha, Madhur K. (East Carolina University, 1988)
Insulin-like growth factor-I (IGF-I) in human hepatoma cells (HEP-G2) has, in addition to its effect on cell growth, shortterm metabolic effects acting through its own receptor. We have demonstrated that normal human hepatocytes, compared with HEP-G2 cells, have virtually no IGF-I binding sites. Because the rate of growth is the major difference between the hepatoma and the normal liver, we asked if normal liver might express IGF-I binding sites under physiologic growth conditions. Indeed, whereas adult rat hepatocytes have low IGF-I binding sites similar to those in human liver, hepatocytes from regenerating liver after 3 d subtotal hepatectomy have an approximately sixfold increase (P < 0.005) and those from fetal rat liver a - 12-fold increase (P < 0.005), to levels comparable to those in the HEP-G2 cells. The specificity of 125I IGF-I binding to its receptor was demonstrated by competition studies with monoclonal antibodies directed toward the IGF-I and the insulin receptors, with unlabeled IGF-I and insulin and by affinity labeling experiments. Thus, if IGF-I has any shortterm metabolic functions in the adult human liver, it is not through interaction with its own receptor. Autocrine regulation by IGF-I of liver growth appears possible since IGF-I binding sites are expressed under pathological and physiological conditions of growth. The mechanism that couples these two phenomena remains to be elucidated. Originally published Journal of Clinical Investigation, Vol. 81, No. 4, Apr 1988
Keywords: IGF-I; Hepatoma cells; Normal liver; Growth rate